Optimization of Dredging Location Determination in Sutami Reservoir Using the Cut and Fill Method - Tri Pambudi; Hari Nugroho; Suripin Suripin (Diponegoro University, 2025)
The Sutami Dam is located on the Brantas River, precisely in Karangkates Village, Sumberpucung District, Malang Regency. The Sutami Dam has been in operation for fifty-one years. Based on observations in the field, the rate of sedimentation entering the Sutami Reservoir is quite high, resulting in shallowing in the reservoir storage area up to the intake gate, which can affect the performance and productive life of the reservoir. This research is conducted to evaluate the planning of mapping dredging locations, the potential sediment that can be dredged, and the increase in the volume capacity of the dredging equipment. This research uses data from bathymetry, which is then analyzed for sedimentation and scour values compared between 2019 and 2022. For soil parameter data, laboratory test results such as grain size analysis and hydrometer analysis are utilized. Data analysis using the cut-fill method in ArcMap 10.8.2 software. The results of this research show that in carrying out dredging activities in the reservoir area, it is necessary to divide the dredging location into two zones with two types of dredgers that have different specifications. To increase the dredging volume capacity in the Sutami Reservoir using the scenario of using two existing dredgers and the addition of two new dredgers, an increase in the dredging capacity in the Sutami Reservoir of 1,702,189.00 m³ per year was obtained.